2018
DOI: 10.1016/j.amsu.2018.03.018
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence occurrence of viral hepatitis and HIV among hemodialysis patients

Abstract: BackgroundPatients with chronic renal failure (CRF) were on maintenance invasive hemodialysis (HD) procedure. This procedure by itself affects immunity of the patients and became more susceptible to viral infections.Aim of the studyto investigate the occurrence of HBV, HCV and HIV infections in patients with hemodialysis.Patients and methodsA retrospective study of 430 end-stage renal failure patients, referred to hemodialysis department at XXXX Teaching Hospital, Baghdad-Iraq from January-2015 to January-2017… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 33 publications
(32 reference statements)
2
6
0
Order By: Relevance
“…In the current study, none of the patients studied were infected with HIV. This finding is similar to the results of a previous study conducted in Baghdad, Iraq (15). The prevalence of HIV among patients on HD was 0% in the Jenin District of Palestine, 6% in Nigeria, and 7% in the US; these rates are much lower than 33% in Kosovo, 39% in Morocco, 50% in France, and 51% in Spain (16).…”
Section: Discussionsupporting
confidence: 89%
“…In the current study, none of the patients studied were infected with HIV. This finding is similar to the results of a previous study conducted in Baghdad, Iraq (15). The prevalence of HIV among patients on HD was 0% in the Jenin District of Palestine, 6% in Nigeria, and 7% in the US; these rates are much lower than 33% in Kosovo, 39% in Morocco, 50% in France, and 51% in Spain (16).…”
Section: Discussionsupporting
confidence: 89%
“…The main treatment for chronic renal disease failure involves an invasive hemodialysis procedure (1). Therefore, patients undergoing dialysis treatment and hemodialysis are at risk of viral infections due to inadequate cellular immunity (2).…”
Section: Introductionmentioning
confidence: 99%
“…Although hemodialysis has increased the durability of patients, it also has exposed the patients to certain viral infections (3). Hemodialysis (HD) patients are at greater risk of the hepatitis B virus (HBV), hepatitis C virus (HCV), and human immunodeficiency virus (HIV) than healthy individuals (1).…”
Section: Introductionmentioning
confidence: 99%
“…We observed that 19% (5/26) of the patients were positive for HBV, HCV or for HIV. It is important to note that these are common in patients undergoing hemodialysis and hence use of personal protective equipment is a must when doing any kind of fistula takedown [ 16 ].…”
Section: Discussionmentioning
confidence: 99%